Effect of Vitamin D on clinical profile of sickled children: A prospective study - Panda, Prakash Chandra; Mishra, Nihar Ranjan; Sa, Bichitra Nanda; Khatua, Amlan; Kumar, Sumit; Nayak, Bijan Kumar (Indian Journal of Child Health, 2020)
Background: Vitamin D status in sickle cell children (SC) has been widely discussed and its effect on clinical profile among SC is currently highly debatable. Objective: The objective of this study was to determine the clinical outcomes in terms of morbidities for Vitamin D supplementation among Vitamin D deficiency (VDD) SC. Materials and Methods: A total of 428 children as per predefined inclusion and exclusion criteria were enrolled in this present prospective study, after receiving written informed parental consent. Patients were supplemented with Vitamin D according to their serum status and followed up at 3 subsequent visits (0, 6, and 12 weeks). All the relevant statistics were done by SPSS v 25.0 (IBM, New York). Results: A total of 428 diagnosed cases of sickle cell anemia were enrolled, from which 272 (63.6%) were male and 156 (36.4%) were female, and 393 cases were found to be VDD (92%). The mean age of the study population was 88.39 (46.27) months. Vitamin D supplementation was significantly associated with decrease in number of vaso-occlusive crisis, duration of hospitalization, and duration of pain hours (p